State of Nature as “Possible Histories” in Thomas Hobbes’ “Civil Science” - Mikhaylovskiy, Aleksandr (Sotsiologicheskoe Obozrenie / Russian Sociological Review, 2024)
The article deals with the Hobbesian state of nature as a foundational model for his epistemic ideal of “civil science.” The first part elucidates the state of nature argument in the context of the Hobbesian “innovative” definition of “civil philosophy” (philosophia civilis) which significantly differs in argumentative standards from contemporary ethics and political philosophy. The second part connects the Hobbesian state of nature and his “natural logic” as specific forms of “first philosophy” concerned with the stabilization of “first definitions” for “civil science”, necessary for “civil science” proper but not a part of it. The third part introduces the state of nature in Hobbes as a “practical” thought experiment made possible by specific observations of our own everyday experience revealed as self-knowledge. Here, the state of nature functions as Hans Vaihingher’s half-fiction, that is, as an informal explanatory model connecting counterfactual possibilities and actuality. The connection occurs in the form of an elaborate “thought experiment” inside actuality, providing not only the counterfactual “limiting case” explaining a range of possible situations, but also a continuum of quasi-narrative descriptions of possible situations and courses of events leading to negative consequences, namely, to controversy in opinions and contention in wills. The fourth part shows how these quasi-narrative descriptions are captured by an understanding of the state of nature model as “possible histories”, providing the basic “range of possibilities” (Spielraum in the sense of Wolfgang von Kries) for Hobbesian “civil science” proper as a science of public right. The state of nature as “Spielraum” allows us to capture specifically political possibilities which form the background for Hobbesian “civil science.” Therefore, the state of nature model provides the “first principles” for the Hobbesian constructive “civil science” in the form of an elaborate probabilistic model.